Features of using the content editor Master Tool by teachers of computer science for creating training applications - M V Kurnosenko (RUDN Journal of Informatization in Education, 2013)
In article experience of use of the cloudy SkyDrive service, the editor of an educational content of Master Tool and the digital book EasySchoolBook is generalized. Within the course «Infoputeshestvy» of subject domain of «Technology» lessons in the 7th class on subjects were conducted: «Data presentation in the computer», «Programming among Skretch».